Structural and neotectonic features of the periadratic depression (Albania) detected by seismic interpretation - SKRAMI, JANI (Bulletin of the Geological Society of Greece, 2001)
The Periadriatic Depression includes the western Lowland of Albania from Vlora to Ulqini. The Periadriatic basin, formed after the main folding and thrusting of Ionian zone, is filled with molasses deposits. The molasse formation building this Depression is made up by Middle Miocene up to Pliocene sediments. The Periadriatic Depression extends on its eastern and southern bordes over folded and thrusted structures of the Ionian and Kruja Zones. The folding and thrusting of Periadriatic Depression is finally due to the Early Pleistocene compressional phase that is evidenced by some important structural unconformities. The Periadriatic Depression is built by some linear relatively narrow anticlines, superimposed over thrust or backthrust faults, and wide synclines. The Mio-Pliocene anticlinal folds generally do not outcrop with all their tectonic elements (flanks,periclines). The positive structures of western coastal part are well expressed on the relief; so, the anticlines here build hills while the synclines are buried under Holocene plains between them. The structural and neotectonic features are evidenced in the seismic lines